ANALISIS PENGGUNAAN JŌKEN HYŌGEN PADA NOVEL“SENSEI HA MAHOUKKAI?” KARYA NAKAMURA KOUZOU (Kajian: Struktur dan Makna) - Rindi Andriani; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2020)
AbstractThis research is a research on the analysis of the structure and meaning of the jyouken hyougen in the novel sensei ha mahoukkai by Nakamura Kouzou. This study aims to determine the types of presupposition expressions contained in Nakamura Kouzo's Sensei Ha Mahoukkai novel, as well as the structure and meaning of these sentences. Data analysis was carried out using descriptive qualitative methods with semantic and sintaksis design based on the theoretical collaboration of Dedi Sutedi, Masuoka and Sunagawa.The results of this study are, there are 35 data of presupposition expressions. among them, 16 data are the jyouken hyougen  of to, 12 data are the jyouken hyougen of tara, and 7 data are the jyouken hyougen of ba. Then, based on the structure, these data generally experience attachment to clauses (S1) and main sentences (S2) in the form of dictionary form verbs, negative verbs, nouns, and adjectives. The most common meanings are, namely, the meaning in the form of cause and effect, habit, the meaning of stating a general event, an event of a natural nature, and how the machine works. Keyword: jyouken hyougen, structure and meaning, Nakamura Kouzou.